The Associations of Cerebrospinal Fluid ApoE and Biomarkers of Alzheimer’s Disease: Exploring Interactions With Sex - Liu, Ying; Song, Jing-Hui; Xu, Wei; Hou, Xiao-He; Li, Jie-Qiong; Yu, Jin-Tai; Tan, Lan; Chi, Song; Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2021)
Background: Sex-related difference in Alzheimer’s Disease (AD) has been proposed and apolipoprotein E (ApoE) isoforms have been suggested to be involved in the pathogenesis of AD. Objective: We aimed to explore whether cerebrospinal fluid (CSF) ApoE is associated with AD biomarkers and whether the associations are different (between sexes). Methods: Data of 309 participants (92 with normal cognition, 148 with mild cognitive impairment (MCI) and 69 with AD dementia) from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) were cross-sectionally evaluated with multiple linear regression model and longitudinally with multivariate linear mixed-effects model for the associations of CSF ApoE with AD biomarkers. Sex-ApoE interaction was used to estimate whether sex moderates the associations of CSF ApoE and AD biomarkers. Results: Significant interactions between CSF ApoE and sex on AD biomarkers were observed (amyloid-β (Aβ): p=0.0169 and phosphorylated-tau(p-tau): p=0.0453). In women, baseline CSF ApoE levels were significantly associated with baseline Aβ (p=0.0135) and total-tau (t-tau) (p<0.0001) as well as longitudinal changes of the biomarkers (Aβ: p=0.0104; t-tau: p=0.0110). In men, baseline CSF ApoE levels were only correlated with baseline p-tau (p<0.0001) and t-tau (p<0.0001) and did not aggravate AD biomarkers longitudinally. Conclusion: The associations between CSF ApoE and AD biomarkers were sex-specific. Elevated CSF ApoE was associated with longitudinal changes of AD biomarkers in women, which indicates that CSF ApoE might be involved in the pathogenesis of AD pathology in a sex-specific way.